What We Want in a Judge - T. J. Mullin (Washington University Journal of Law & Policy, 2017)
This Article recognizes the current state of bankruptcy courts and the qualities that make Judge Barry Schermer a quintessential figure in adjudicating these types of cases. Mullin describes important qualities needed in a bankruptcy judge including morality and integrity, as well as versatility and predictability, among others. The Author confirms these qualities in Judge Schermer, as well the additional qualities of patience and the ability to reverse a decision he feels was incorrect.
Keywords: Bankruptcy; Bankruptcy Court; Debtors; Judge Schermer